THE SIGNIFICANCE OF PRIMARY AND SECONDARY CHARACTERS IN JACK LONDON'S NOVEL “MARTIN EDEN” TO EXPRESS THE AUTHOR'S LITERARY CONCEPTION - Karimova, Munira (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
The article deals with the concepts of artistic image and conception. In particular, the importance of primary and secondary characters in expressing the author's artistic conception was analyzed on the example of Jack London's novel "Martin Eden". The role of main and secondary (auxiliary) images, classified according to their function in bringing out the idea expressed in the novel and their place in the texture of the artistic work, was discussed. The main character, who stands in the center of the events, sets the plot in motion and carries the main idea the writer wants to express, Martin's inner and outer portrait were interpreted based on the criterion of reflecting the essence of the human psyche, its leading features covering all its complexity from the point of view of the aesthetic ideal of the creator. Sometimes there are two or more images of equal importance in the center of the work. For example, in "Martin Eden" the characters of Martin and Ruth are in the leading place. These are major or adjacent characters, one of which serves to vividly express the character of the other. In an artistic work, characters with relatively little participation- episodic characters or supporting characters representing a certain idea — are mainly united around the main character. In the novel "Martin Eden", the writer effectively used secondary characters to reveal the microchronotope of the main character. Jack London's skill of image creation was analyzed through psychological and autobiographical methods.
Keywords: artistic image; conception; main character; secondary hero; biographical image; inner world; novel